2010
DOI: 10.1186/1743-7075-7-8
|View full text |Cite
|
Sign up to set email alerts
|

A low α-linolenic intake during early life increases adiposity in the adult guinea pig

Abstract: BackgroundThe composition of dietary fatty acids (FA) during early life may impact adult adipose tissue (AT) development. We investigated the effects of α-linolenic acid (ALA) intake during the suckling/weaning period on AT development and metabolic markers in the guinea pig (GP).MethodsNewborn GP were fed a 27%-fat diet (w/w %) with high (10%-ALA group), moderate (2.4%-ALA group) or low (0.8%-ALA group) ALA content (w/w % as total FA) until they were 21 days old (d21). Then all animals were switched to a 15%-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 43 publications
(55 reference statements)
0
8
0
2
Order By: Relevance
“…A study investigating the impact of differing ALA contents in neonatal guinea pigs using LA to primarily offset energy contribution of ALA found that 3 weeks of low ALA feeding (0.8 % total fat) (high LA feeding) followed by a chow diet for 16 weeks resulted in a 15% increase in fat mass at 19 weeks of age. In addition these animals had higher adipose tissue proliferation rates than those fed an isoenergetic (with matched fat content) 10% ALA diet [111]. Though the animals in this study were not fed by their mothers, it is possible to infer the effect of feeding a low ALA/high LA diet in the early postnatal period on subsequent body composition and adipocyte proliferation.…”
Section: Linoleic Acid and Early Life Obesity Developmentmentioning
confidence: 91%
“…A study investigating the impact of differing ALA contents in neonatal guinea pigs using LA to primarily offset energy contribution of ALA found that 3 weeks of low ALA feeding (0.8 % total fat) (high LA feeding) followed by a chow diet for 16 weeks resulted in a 15% increase in fat mass at 19 weeks of age. In addition these animals had higher adipose tissue proliferation rates than those fed an isoenergetic (with matched fat content) 10% ALA diet [111]. Though the animals in this study were not fed by their mothers, it is possible to infer the effect of feeding a low ALA/high LA diet in the early postnatal period on subsequent body composition and adipocyte proliferation.…”
Section: Linoleic Acid and Early Life Obesity Developmentmentioning
confidence: 91%
“…Recent studies (24) have shown that perinatal exposure to a rich n-6 FA diet is able to induce obesity and to affect body fat mass across generations. On the other hand, the beneficial role of dietary n-3 FA during early life has been emphasized because n-3 FA deficiency increases adiposity in guinea pigs (25). This idea was reinforced by the study of Massiera et al (26), showing that the addition of a-linolenic acid (a-LNA [or C18:3n-3]) to an LA-rich high-fat diet (HFD) under isolipidic and isocaloric conditions reduces the deleterious Figure 1-Schematic illustration of the pathways for biosynthesis and degradation of ECs (A) and the experimental study design (B).…”
mentioning
confidence: 99%
“…According to the recent review by Kim and Ilich (2011) [22], osteoporotic animals given ALA-rich diets showed improved bone properties, which was strengthened when combined with estrogen therapy or in various pathological conditions. Furthermore, in some animal studies ALA-rich diets resulted in a significant reduction in body weight, visceral adiposity and leptin [12,23], whereas ALA- deficient diets led to a significant increase in hepatic de novo lipogenesis, total/epididymal fat mass and adipocyte proliferation [24]. The increase of adipose tissue observed in obesity involves both hypertrophy of pre-existing adipocytes and hyperplasia by forming new adipocytes from precursor cells (adipogenesis) [25,26].…”
Section: Discussionmentioning
confidence: 99%